2016
DOI: 10.5604/17331331.1215610
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Biofilm Formation and Wide Distribution of Virulence Associated Genes among Vibrio spp. Strains Isolated from the Monastir Lagoon, Tunisia

Abstract: A b s t r a c tIn the current study, 65 Vibrio spp. were isolated from the Monastir lagoon water, were characterized phenotypically and genotypically. In addition, we looked for the presence of three Vibrio parahaemolyticus virulence genes (tlh, trh and tdh) and ten Vibrio cholerae virulence genes (ctxA, vpi, zot, ace, toxR, toxT, tosS, toxRS, tcpA and cpP). We also investigated the antibiotic susceptibilities and the adherence ability of the identified strains to abiotic material and to biotic surfaces. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…This approximately 7-kb pathogenic island carries ctxAB, zot, ace, cep, and orfU genes (5). It has been reported that the zot gene encodes a zonula occludens toxin that increases transcellular ion transport and contributes to diarrhea in cholera, whereas the ace gene encodes an accessory cholera enterotoxin that disturbs small-intestinal tight junction permeability (11,18,20). In addition, previous studies have indicated that a cri gene is an important virulence-related gene required for toxin-linked cryptic plasmid replication in V. cholerae (26), whereas a nanH gene encodes a neuraminidase that is a key factor in the infectious process of many viruses and pathogenic bacteria (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This approximately 7-kb pathogenic island carries ctxAB, zot, ace, cep, and orfU genes (5). It has been reported that the zot gene encodes a zonula occludens toxin that increases transcellular ion transport and contributes to diarrhea in cholera, whereas the ace gene encodes an accessory cholera enterotoxin that disturbs small-intestinal tight junction permeability (11,18,20). In addition, previous studies have indicated that a cri gene is an important virulence-related gene required for toxin-linked cryptic plasmid replication in V. cholerae (26), whereas a nanH gene encodes a neuraminidase that is a key factor in the infectious process of many viruses and pathogenic bacteria (9).…”
mentioning
confidence: 99%
“…In this study, based on the previous research, the LAMP method was applied for the first time in detection of four important virulence-related genes-ace, zot, cri, and nanH-of V. cholerae. The former two genes contribute to diarrhea in pandemic cholera (11,18,20), whereas the cri and nanH genes are key factors required for toxins (26) and the infectious process of many viruses and pathogenic bacteria (9), respectively. Inner, outer, and loop probes were designed and synthesized to target each of these genes.…”
mentioning
confidence: 99%